APPLICATION OF REFRIGERATED AND FROZEN SORGHUM MALT SLURRIES IN THE PRESERVATION OF STARTER CULTURES FOR OBUSHERA FROM UGANDA - Ivan Muzira Mukisa; Stellah Byakika; Arnold Serwanga (University of Sultan Ageng Tirtayasa, 2020)
Industrial production of traditional fermented beverages is limited by lack of quality commercial starter cultures. Saccharomyces cerevisiae MNC21Y and Lactobacillus plantarum MNC21 can be used to ferment cereal beverages such as Obushera. These cultures are unavailable as commercial starters due to lack of appropriate propagating and distributing procedures. The purpose of this study was to evaluate the use of refrigerated and frozen sorghum slurries as carrier media for the starters. Starters were propagated in sorghum slurries (30°C for 24 h) and stored at 5°C and -18°C for 90 days. Viability of Saccharomyces cerevisiae and Lactobacillus plantarum was determined by cell counts after surface plating and pour plating, respectively. Fermentation ability was determined by inoculating sorghum slurries with starters and monitoring pH, acidity and flavor development. Viability was higher for starters stored at 5°C (S. cerevisiae: 6 log cfu.g-1 and Lb. plantarum: 7-9 log cfu.g-1during 90 days) than those at -18°C (S. cerevisiae: 2 cfu.g-1 and Lb. plantarum: 4 log cfu.g-1after 30 days). Refrigerated starters acidified Obushera (pH £ 4.5) faster (10-20 h) than frozen ones (18-24 h). Refrigerated or frozen S. cerevisiae + Lb. plantarum starters in sorghum malt slurries can remain viable for at least one or three months, respectively and produce Obushera with characteristic flavors.